Principais aspectos estruturais e espeleológicos das cavernas em mármores da formação alcantil, localizadas na Serra do Canudo em Santa Quitéria/CE - Luz, Ana Angélica Gomes (2024)
The Serra do Canudo, located in the southeast region of the municipality of Santa Quitéria in Ceará State, presents caves developed in Neoproterozoic carbonate metasedimentary rocks of the Alcantil Formation and this research had as main objective to identify and study the main structural and speleological aspects that contributed to the karstification process and genesis of the caves. In order to understand the configuration of the karst relief in the marbles, a detailed morphological mapping and geological structures were carried out. Through the mapping of the caves, it was possible to verify that the geometric pattern of fracturing was orthogonal and to register seven brittle structures present, located in the ceilings, which follow the same orientation as the conduits. The lineaments are arranged in N- S and W-E directions and the spatial orientation of the structures present on the surface coincides with those mapped in the subsurface. This information suggests that the N-S and W-E discontinuities are more penetrating and that they have larger openings, allowing the infiltration and circulation of meteoric waters. Thus, the differential dissolution of the marble in depth along the fracture planes conditioned the formation of the natural cavities studied and the soil observations show that the mapped lineaments are constituted by vertical fractures. In order to understand the sedimentation processes, cave formation environments and where they are geologically inserted, the tufa deposits and speleothems in three caves were mapped and characterized. Among the caves studied, the cave classified as cave E16, presented the most relevant speleological attributes, presenting typological varieties of speleothems, such as stalagmites, tubular stalactites and helectites, the latter being extremely rare and never described in the studied region and occurring from restricted way in this cave. Tufa deposits that contain fossil and partly preserved records of plants and shells were mapped and, through field observations associated with petrographic analysis, it was possible to identify these tufas, as micritic, intraclastic, phytoclastic and micritic/phytoclastic tufas.